Tomorrow's world: current developments in the therapeutic use of technology for psychosis. (September 2016) - O'Hanlon, Puffn; Aref-Adib, Golnar; Fonseca, Andres; Lloyd-Evans, Brynmor; Osborn, David; Johnson, Sonia
Summary: There is now an established evidence base for the use of information and communication technology (ICT) to support mental healthcare ('e-mental health') for common mental health problems. Recently, there have been significant developments in the therapeutic use of computers, mobile phones, gaming and virtual reality technologies for the assessment and treatment of psychosis. We provide an overview of the therapeutic use of ICT for psychosis, drawing on searches of the scientific literature and the internet and using interviews with experts in the field. We outline interventions that are already relevant to clinical practice, some that may become available in the foreseeable future and emerging challenges for their implementation.